Advanced Magnetic Resonance Imaging Techniques in Management of Brain Metastases - Mehrabian, Hatef; Detsky, Jay; Soliman, Hany; Sahgal, Arjun; Stanisz, Greg J. (Frontiers in Oncology, 2019)
Brain metastases are the most common intracranial tumours and occur in 20-40% of all cancer patients. Lung cancer, breast cancer, and melanoma are the most frequent primary cancer to develop brain metastases. Treatment options include surgical resection, whole brain radiotherapy, stereotactic radiosurgery and systemic treatment such as targeted or immune therapy. Anatomical magnetic resonance imaging (MRI) of the tumour (in particular post-Gadolinium T1-weighted and T2-weighted FLAIR) provide information about lesion morphology and structure, and are routinely used in clinical practice for both detection and treatment response evaluation for brain metastases. Advanced MRI biomarkers that characterize the cellular, biophysical, micro-structural and metabolic features of tumours have the potential to improve the management of brain metastases from early detection and diagnosis, to evaluating treatment response. Magnetic resonance spectroscopy (MRS), chemical exchange saturation transfer (CEST), quantitative magnetization transfer (qMT), diffusion-based tissue microstructure imaging, trans-membrane water exchange mapping, and magnetic susceptibility weighted imaging (SWI) are advanced MRI techniques that will be reviewed in this article as they pertain to brain metastases.